EFFECT OF SAND FRACTION ON THE BEHAVIOUR OF SAND-BENTONITE MIXTURES - Agus Setyo Muntohar, Roslan Hashim (Jurnal Rekayasa Sipil, 2008)
Understanding characteristics of soil mixtures lead to increasing the confidence level before applying such materials in the field. The outcomes of this study can provide insight into the index properties and swelling – compressibility behaviour of sand – bentonite mixtures, between non-swelling materials and swelling materials. Series of laboratory tests were conducted to evaluated index properties, compaction, strength, and swelling behaviour of the sand – bentonite mixtures. The result of this study indicated that the existence of bentonite in the soil mixtures influence the swelling behaviour, which follows hyperbolic curve model. Amount and size of non swelling fraction reduced the swelling and compressibility of expansive soils.